2007
DOI: 10.1117/12.699797
|View full text |Cite
|
Sign up to set email alerts
|

Experienced quality factors: qualitative evaluation approach to audiovisual quality

Abstract: Subjective evaluation is used to identify impairment factors of multimedia quality. The final quality is often formulated via quantitative experiments, but this approach has its constraints, as subject's quality interpretations, experiences and quality evaluation criteria are disregarded. To identify these quality evaluation factors, this study examined qualitatively the criteria participants used to evaluate audiovisual video quality. A semi-structured interview was conducted with 60 participants after a subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 24 publications
6
52
0
Order By: Relevance
“…The results from the repeated measures ANOVA test show that the effects of the two factors under consideration, as well as the interaction effects between them are statistically significant. Thus, as previous research (Ghinea and Thomas, 1998;Jumisko-Pyykkö et al, 2007) and the results from the earlier experiments reported in this research work have shown (Ghinea and Ademoye 2010; Ghinea and Ademoye, in press) content has a significant impact on users' perception of multimedia (F=3.989, p=0.002). More importantly, however, the association between olfactory media content and audiovisual content in the olfaction-enhanced videos was also found to be significant, and consequently impacts on the perceived sense of relevance of the olfactory media (F=42.965, p=0.000).…”
Section: Impact Of Associating Smell With Content On the Perceived Sesupporting
confidence: 61%
“…The results from the repeated measures ANOVA test show that the effects of the two factors under consideration, as well as the interaction effects between them are statistically significant. Thus, as previous research (Ghinea and Thomas, 1998;Jumisko-Pyykkö et al, 2007) and the results from the earlier experiments reported in this research work have shown (Ghinea and Ademoye 2010; Ghinea and Ademoye, in press) content has a significant impact on users' perception of multimedia (F=3.989, p=0.002). More importantly, however, the association between olfactory media content and audiovisual content in the olfaction-enhanced videos was also found to be significant, and consequently impacts on the perceived sense of relevance of the olfactory media (F=42.965, p=0.000).…”
Section: Impact Of Associating Smell With Content On the Perceived Sesupporting
confidence: 61%
“…This approach also allows more flexibility in data collection because follow-up questions can be asked [32], which is not possible with questionnaires. Collecting descriptive data from interviews could be beneficial when the research field is relatively unexplored [20].…”
Section: Collection Of Datamentioning
confidence: 99%
“…Jumisko-Pyykkö et al [20] used aqualitative approach to evaluate audio-visual quality by combining asingle-stimulus method, for quality evaluation, with semi-structured interviews, to establish quality evaluation criteria. The data analysis combined aq ualitative analysis based on grounded theory and aq uantitative statistical analysis, Bayesian modelling.…”
Section: Earlier Research On Perceiveda Udio and Video Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given a bit rate constraint, the video can be encoded with different parameters by different video coding codecs; and the variations eventually lead to divergent user-perceived video qualities (Ahmad, 2006b;Cranley, Murphy & Perry, 2004;Kun, Richard & Shih-Ping, 2001;Song, Tjondronegoro & Azad, 2010). Audio quality, including the volume, sampling rate, bit rate of the audio, often takes effects with the usage ambient (e.g., noisy or quiet) and the content type (e.g., music videos) together (JumiskoPyykkö, Häkkinen & Nyman, 2007). Delivery strategy is about how the video service is delivered to the user.…”
Section: Systemmentioning
confidence: 99%